Local government politics in local press 1979 - Brantgärde, Lennart (University of Gothenburg, 1982)
This survey is part of the research program ´Local government - an evaluation of the reform of amalgamation of municipalities´. The purpose was to illustrate the treatment of the local press of local politics in 1979. In the coding all material, except private advertising, that touched the municipality in question has been observed, and after that a further classification has been made according to whether this local material could be regarded as treating various aspects of the local policy.

This survey is part of the research program ´Local government - an evaluation of the reform of amalgamation of municipalities´. The purpose was to illustrate the treatment of the local press of local politics in 1979. In the coding all material, except private advertising, that touched the municipality in question has been observed, and after that a further classification has been made according to whether this local material could be regarded as treating various aspects of the local policy.
Kommunalpolitik i ortspressen 1979
Keywords: internal politics; inrikespolitik; Media; Media; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap